PENTINGNYA MEMAHAMI ETIKA DALAM MENGAMBIL DAN MENGOLAH DATA - Saputra, Faris Sandra; Pamungkas, Adhi Yoga Muris; Faisal, Syafrie Dwi; T, MHD Raihan Natigor; Rakhmawati, Nur Aini (Jurnal Komunikasi Profesional, 2019)
In today's technological era, most human activities are closely related to digitalization. This causes data growth to increase dramatically. The potential for data dissemination is also very wide open, so that as the owner of personal data and active technology users, many people are worried that their data is not used properly by the parties concerned about the benefits, fairness, approval and confidentiality. Therefore a number of written rules were made such as Article 32 of the ITE Law relating to data use interference as a basis for rules. The importance of having an understanding and knowledge related to ethical basis and data processing methods is also necessary as a technical guide to direct all data processing activities. However, there are still many parties who ignore the rule. It is not true that the process of retrieving and processing data also makes the final result not in accordance with the original goal. In this paper we will explain some examples of technical data collection and processing methods. A description of ethical theory will also be given. Then the challenges and principles in data collection and processing will be written. The hope of this paper can make the data users involved can use the data as they should according to applicable ethics, methods and laws.Keywords: Data, Data Collection, Data Processing, Ethics, Data Ethics